Evaluation of Ventricular Diastolic Function in Patients With Fibromyalgia Syndrome - Selçuk SAYILIR,; Gökhan ERGÜN,; Timur EKİZ, (Archives of Rheumatology, 2018)
Objectives: This study aims to compare the diastolic functions between fibromyalgia (FM) patients and control subjects by using transthoracic echocardiography. Patients and methods: This case-control and cross-sectional study included 34 female FM patients (mean age 43.6±8.2 years; range 28 to 57 years), who were diagnosed by The American College of Rheumatology 1990 Criteria for the Classification of Fibromyalgia and defined as the FM group. A control group was defined consisting of 30 healthy females (mean age 41.2±9.1 years; range 22 to 54 years). Echocardiography findings of the groups were compared. Results: The body mass index and mean disease duration of the FM group were 25.37±2.71 kg/m2 and 12.24 months, respectively. The body mass index of the control group was 25.58±1.49 kg/m2. There was no significant difference between the groups in terms of age and body mass index. Isovolumetric relaxation time and mitral E-wave deceleration time values were significantly higher in the FM group than in the control group (p=0.047, p=0.003, respectively). Conclusion: Isovolumetric relaxation time and mitral valve deceleration time are significantly prolonged in FM patients compared with healthy subjects. Female patients with FM seem to be under risk of impaired relaxation and diastolic function of the left ventricle.